PENGARUH DESAIN LOGO DAN NAMA MEREK TERHADAP BRAND IMAGE MIXUE (Studi Kasus Pada Mahasiswa STIE Wibawa Karta Raharja) - Dewi Puspasari (Sekolah Tinggi Manajemen IMMI Jakarta, 2023)
One of the company's strategies in conveying messages regarding product information to be offered is by means of promotion. Promotion is carried out in order to convey product advantages and product benefits so that it is expected to influence consumers to buy. Promotion is an important factor in the marketing mix used by companies to win market competition. Brand identity will make consumers recognize and associate a company. All elements and parts of the brand have a function to form a brand identity so that it will create awareness and brand image. Mixue tries to build a brand image for its products so that it can influence consumers in terms of purchasing decisions and will have brand awareness values for consumers who have bought their products. Brand image is what consumers think and feel when they hear or see a brand, the more famous a brand is, the easier it will be for consumers to recognize the product so that it will make the company gain profits, increase sales figures and dominate market share. This study aims to determine the influence of logo design and brand name to brand image Mixue. The number of samples used in this study amounted to 144. This type of research is quantitative with the data analysis method used using multiple linear regression. The results of this study found that there was an influence of logo design and brand name on brand image of 40.4%.